IMPACT OF PRE AND POST-CALVING BODY CONDITION SCORE CHANGE ON REPRODUCTION TRAITS OF MONTBELIAD COWS IN ALGERIAN SEMI ARID AREA - C. E. Mouffok; L. Semara; T. Madani; H. Debeche; F. Belkasmi (Journal of Animal and Plant Sciences, 2013)
This study aimed to determine the relationships between body condition score (BCS) and its change around calving and the reproduction traits. A total of 220 Montbeliard dairy cows reared in four farms whose level of breeding proficiency is acceptable were included in this study. Body condition (BC) in dry and postpartum period was assessed monthly on a scale of 1 to 5. Eight reproductive parameters were recorded or calculated. The results show a significant decrease (p 0.05).
Keywords: BCS; Reproduction traits; Cow; dry; post-partum; semi arid